Granular cell tumour (a case report) - (:unkn) unknown (My University, 1997)
The granular cell tumour (GCT) is a relatively uncommon neoplasm that shows a predilection for the oral cavity, especially the tongue. The tumour usually presents as a slow-growing, non-ulcerated nodular mass. It is most common in young and middle-aged adults and is twice as common in women as in men. Some studies have shown it to be relatively more common in coloured people. Multiple granular cell tumours occasionally may occur. Treatment consists of local surgical excision; recurrence is uncommon. This case report presents a case of GCT in a 32 years old woman's tongue and its treatment.
Keywords: Adult; Female; Humans; Tongue; Tongue Neoplasms; Granular Cell Tumor